2019
DOI: 10.21511/imfi.16(2).2019.07
|View full text |Cite
|
Sign up to set email alerts
|

The effect of IFRS adoption on the value relevance of accounting information: evidence from South Korea

Abstract: This study investigates whether the value relevance of accounting information was changed after IFRS adoption in South Korea. Related prior studies have found mixed empirical evidence depending on research methodologies or research periods. Moreover, the effect of IFRS adoption on value relevance can be different between Korean stock markets (KSE and KOSDAQ) because they have different characteristics. Also, the main financial statements reported by Korean firms had changed from individual financial statements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 18 publications
0
0
0
Order By: Relevance
“…These guidelines carry significant importance for investors, creditors, and other stakeholders as they seek to evaluate a company's financial well-being (Lawal et al, 2020;Salah and Abdel-Salam, 2019). In light of the escalating complexity surrounding financial reporting, it has become indispensable for companies to provide reports that are both detailed and easily comprehensible (Do et al, 2019). By adhering to this standard, companies ensure that investors, creditors, and other stakeholders can access the information necessary for making informed decisions (Sun et al, 2021).…”
Section: Ifrs 17 and Understandability Of The Financial Reportsmentioning
confidence: 99%
“…These guidelines carry significant importance for investors, creditors, and other stakeholders as they seek to evaluate a company's financial well-being (Lawal et al, 2020;Salah and Abdel-Salam, 2019). In light of the escalating complexity surrounding financial reporting, it has become indispensable for companies to provide reports that are both detailed and easily comprehensible (Do et al, 2019). By adhering to this standard, companies ensure that investors, creditors, and other stakeholders can access the information necessary for making informed decisions (Sun et al, 2021).…”
Section: Ifrs 17 and Understandability Of The Financial Reportsmentioning
confidence: 99%
“…The findings revealed that conditional conservatism was positively (negatively) related to value relevance prior to (post) mandatory IFRS adoption. Ki, Leem and Yuk (2019) investigated whether the value relevance of accounting information changed after IFRS adoption in South Korea. Related prior studies had found mixed empirical evidence depending on research methodologies or research periods.…”
Section: Empirical Reviewmentioning
confidence: 99%